Functional Trajectories of Persons with Cardiovascular Disease in Late Life. Issue 1 (21st November 2018) - Keeney, Tamra; Fox, Annie B.; Jette, Diane U.; Jette, Alan
Abstract : Objectives: Physical function declines with aging and is accelerated for persons with cardiovascular disease (CVD). While CVD increases the risk of functional decline in late life, little is known about differences in trajectories of functional decline. To determine whether there is more than 1 trajectory of functional decline in Americans with cardiovascular disease (CVD) who are functionally independent. Design: Secondary analysis of National Health and Aging Trends Study (NHATS). Latent class growth modeling was used to estimate trajectories of function over 4 years of follow‐up. Setting: Annual structured in‐home interviews. Participants: Americans aged 65 and older with CVD who were functionally independent at baseline (N = 392). Measurements: We compared trajectories of function in individuals with CVD with trajectories of those without and examined the association between risk factors (sex, age at baseline, education level, comorbidity) and trajectory group membership. Function was measured using the Short Physical Performance Battery. Results: Three functional trajectories emerged: rapid functional decline (23.8%), gradual functional decline (44.2%), and stable function (32.0%). Similar trajectories were seen for those without CVD, with a smaller proportion in the rapid functional decline group (16.2%). Women, older participants, and those with less education and greater comorbidity were less likely to be in the stable function group than the rapid functional decline group. Conclusion: Although function declines in late life for independently functioning persons with CVD, some individuals remain stable, and others decline gradually or rapidly. Persons with CVD were more likely to experience rapid functional decline than those without, suggesting that CVD increases the risk of rapid functional decline. Risk factors predicted functional trajectory group membership, not just overall decline.J Am Geriatr Soc 67:37–42, 2019.